Prostigmata (Acari: Trombidiformes) as biological control agents - Hernandes, Fabio A. [UNESP]; de Castro, Tatiane Marie M. G.; Venancio, Renan (My University, 2015)
Prostigmata is the larger of the two suborders of the order Trombidiformes within the superorder Acariformes. This suborder constitutes a large assemblage of morphologically, biologically and ecologically diverse groups consisting of 36 superfamilies, some of which consist largely of predatory or parasitic species. In relation to the groups treated in this chapter, most studies concerning the potential as natural enemies of pest organisms refer to the Bdelloidea, Pyemotoidea and Tarsonemoidea. However, these studies are usually limited, conducted by a reduced number of specialists, usually from restricted geographic areas. They involve mainly laboratory trials, with rare consistent attempts toward the expansion of the work to conditions more similar to the habitats in which those natural enemies are expected to be used. Considering the behavior and biological characteristics of the different groups discussed in this chapter, several species have shown good potential for practical use. It seems that the main obstacle to the expansion of the efforts dedicated to the discovery of promising prostigmatid natural enemies is the lack of trained personnel to conduct the research work. New stimulus to the study of biodiversity in some countries might lead to the conduction of solid and comprehensive projects to determine species with good qualities in biological control.
Keywords: Bdelloidea; Cheyletoidea; Erythraeioidea; Pyemotoidea; Raphignathoidea; Tarsonemoidea; Tydeoidea